Oral curcumin ameliorates acute murine campylobacteriosis - Heimesaat, Markus M.; Mousavi, Soraya; Lobo de Sá, Fábia Daniela; Peh, Elisa; Schulzke, Jörg-Dieter; Bücker, Roland; Kittler, Sophie; Bereswill, Stefan (Frontiers in Immunology, 2024)
Human infections with the food-borne enteropathogen Campylobacter jejuni are responsible for increasing incidences of acute campylobacteriosis cases worldwide. Since antibiotic treatment is usually not indicated and the severity of the enteritis directly correlates with the risk of developing serious autoimmune disease later-on, novel antibiotics-independent intervention strategies with non-toxic compounds to ameliorate and even prevent campylobacteriosis are utmost wanted. Given its known pleiotropic health-promoting properties, curcumin constitutes such a promising candidate molecule. In our actual preclinical placebo-controlled intervention trial, we tested the antimicrobial and anti-inflammatory effects of oral curcumin pretreatment during acute experimental campylobacteriosis.Methods: Therefore, secondary abiotic IL-10 -/-mice were challenged with synthetic curcumin via the drinking water starting a week prior oral C. jejuni infection. To assess anti-pathogenic, clinical, immune-modulatory, and functional effects of curcumin prophylaxis, gastrointestinal C. jejuni bacteria were cultured, clinical signs and colonic histopathological changes quantitated, pro-inflammatory immune cell responses determined by in situ immunohistochemistry and intestinal, extra-intestinal and systemic pro-inflammatory mediator measurements, and finally, intestinal epithelial barrier function tested by electrophysiological resistance analysis of colonic ex vivo biopsies in the Ussing chamber.Results and Discussion: Whereas placebo counterparts were suffering from severe enterocolitis characterized by wasting symptoms and bloody diarrhea on day 6 post-infection, curcumin pretreated mice, however, were clinically far less compromised and displayed less severe microscopic inflammatory sequelae such as histopathological changes and epithelial cell apoptosis in the colon. In hat formatiert: Schriftart: Kursiv addition, curcumin pretreatment could mitigate pro-inflammatory innate and adaptive immune responses in the intestinal tract and importantly, rescue colonic epithelial barrier integrity upon C. jejuni infection. Remarkably, the disease-mitigating effects of exogenous curcumin was also observed in organs beyond the infected intestines and strikingly, even systemically given basal hepatic, renal, and serum concentrations of pro-inflammatory mediators measured in curcumin pretreated mice on day 6 post-infection. In conclusion, the anti-Campylobacter and disease-mitigating including antiinflammatory effects upon oral curcumin application observed here highlight the polyphenolic compound as a promising antibiotics-independent option for the prevention from severe acute campylobacteriosis and its potential post-infectious complications.